The Association of Perceived Labor Agentry and Depression and/or Anxiety - Whelan, Anna R.; Recabo, Olivia; Ayala, Nina K.; Clark, Melissa A.; Lewkowitz, Adam K. (American Journal of Perinatology, 2023)
Objective Pregnancies complicated by perinatal mood disorders or a history of mental health disorder are at increased risk for complications including postpartum depression/anxiety. Patients' perceived control over childbirth is known to be an important factor for development of postpartum depression/anxiety. It is unclear whether women with preexisting and/or current depression and/or anxiety have different perceptions of control during childbirth compared with those without these comorbidities. This study aimed to evaluate the association between a current and/or prior diagnosis of depression and/or anxiety and scores on the Labour Agentry Scale (LAS), a validated tool evaluating patient's experience of control over their labor and delivery.Study Design This is a cross-sectional study of nulliparous patients admitted at term to a single center. Participants completed the LAS after delivery. A trained researcher performed detailed chart reviews for all participants. Participants were identified as having a current or historical diagnosis of depression/anxiety by self-report confirmed by chart review. Scores on the LAS were compared between those with versus without a diagnosis of depression/anxiety prior to admission for delivery.Results A total of 73 (44.8%) of the 149 participants held a current and/or prior diagnosis of depression and/or anxiety. Baseline demographics were similar between those with and without depression/anxiety. Mean scores on the LAS (range: 91–201) were significantly lower for those with depression/anxiety than those without a prior diagnosis (150.0 vs. 160.5, p < 0.01). Even after controlling for mode of delivery, admission indication, anesthesia, and Foley balloon usage, participants with anxiety and depression had scores that were on average 10.4 points lower on the LAS (95% confidence interval: −19.25, −1.62).Conclusion Participants with a current and/or prior diagnosis of depression and/or anxiety scored lower on the LAS as compared with those without psychiatric diagnoses. Patients with psychiatric diagnoses may benefit from increased education and support during childbirth.Key Points
Keywords: depression; anxiety; labor; postpartum depression; perinatal mental health